2012
DOI: 10.1016/j.jhep.2012.07.008
|View full text |Cite
|
Sign up to set email alerts
|

CXCR3-dependent recruitment and CCR6-mediated positioning of Th-17 cells in the inflamed liver

Abstract: Background & AimsIL-17 secreting CD4 (Th17) and CD8 (Tc17) T cells have been implicated in immune-mediated liver diseases, but the molecular basis for their recruitment and positioning within the liver is unknown.MethodsThe phenotype and migratory behaviour of human liver-derived Th17 and Tc17 cells were investigated by flow cytometry and chemotaxis and flow-based adhesion assays. The recruitment of murine Th17 cells to the liver was studied in vivo using intra-vital microscopy.ResultsIL-17+ T cells comprised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
190
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(201 citation statements)
references
References 36 publications
11
190
0
Order By: Relevance
“…This scenario is supported by recent data in mice showing that the expansion and differentiation of Th17 cells in the gut were controlled by an IL-17A-dependent production of CCL20 in gut mucosa (46). Indeed, we observed that Liv-MAIT cells produced both IL-17A and CCL20, supporting the possible role for MAIT cells in the liver-driven recruitment of inflammatory CCR6 + Th17 cells (27,28).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This scenario is supported by recent data in mice showing that the expansion and differentiation of Th17 cells in the gut were controlled by an IL-17A-dependent production of CCL20 in gut mucosa (46). Indeed, we observed that Liv-MAIT cells produced both IL-17A and CCL20, supporting the possible role for MAIT cells in the liver-driven recruitment of inflammatory CCR6 + Th17 cells (27,28).…”
Section: Discussionsupporting
confidence: 89%
“…We also observed that intrahepatic MAIT cells were the T cell subset primarily able to secrete CCL20 (Fig. 5B), the known ligand of CCR6, which is expressed on Th17 (27,28) and MAIT cells (Supplemental Fig. 3).…”
Section: Il-17a-producing T Cells In the Intrahepatic Environment Arementioning
confidence: 64%
“…However, Chuang et al [16] have already demonstrated their presence in the portal tract of PBC patients. Moreover, a very recent paper has demonstrated that Tregs not only express CXCR3, but also Th17 and Tc17 + lymphocytes [17]. These findings suggest that a future detailed quantitative study is necessary to clarify the situation.…”
Section: Discussionmentioning
confidence: 96%
“…The proinflammatory chemokines CXCL-9-11 are involved in the recruitment of CXCR3 + , CD4 + , and CD8+ T cells and are known to be expressed by hepatocytes, cholangiocytes, and stellate cells (29,30). Furthermore, IL-17 has been demonstrated to increase the expression of chemokines, such as CXCL-9, CXCL-11, and CCL-20, by biliary epithelial cells (29)(30)(31). Therefore, it was possible that the increased IL-17 expression by female lymphocytes could feed chemokine secretion by liver cells, which in turn could lead to the recruitment of lymphocytes into portal tracts (31).…”
Section: Increased Expression Of the Chemokines Cxcl-9 And Cxcl-10 Inmentioning
confidence: 99%
“…Furthermore, IL-17 has been demonstrated to increase the expression of chemokines, such as CXCL-9, CXCL-11, and CCL-20, by biliary epithelial cells (29)(30)(31). Therefore, it was possible that the increased IL-17 expression by female lymphocytes could feed chemokine secretion by liver cells, which in turn could lead to the recruitment of lymphocytes into portal tracts (31). In female livers, the expression of CXCL-9 and CXCL-10 was found to be significantly increased as compared with male livers.…”
Section: Increased Expression Of the Chemokines Cxcl-9 And Cxcl-10 Inmentioning
confidence: 99%